Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2020)
I am pleased to have recently taken on the role of Executive Director (Acting) of ORNAC. While my experience of seven years in OR Management has served me well there are many aspects of the business world that are new to me and challenging. It will be quite a learning curve. My role includes managing the day-to-day business of ORNAC - I receive and respond to emails to info@ornac.ca and phone calls, manage the member database and ORNAC boutique, and provide assistance to ORNAC committees.